Daytime light exposure is a strong predictor of seasonal variation in sleep and circadian timing of university students. Issue 2 (7th December 2022) - Dunster, Gideon P.; Hua, Isabelle; Grahe, Alex; Fleischer, Jason G.; Panda, Satchidananda; Wright, Kenneth P.; Vetter, Céline; Doherty, Jennifer H.; de la Iglesia, Horacio O.
Abstract: In the absence of electric light, sleep for humans typically starts soon after dusk and at higher latitudes daily sleep timing changes seasonally as photoperiod changes. However, access to electric light shields humans from natural photoperiod changes, and whether seasonal changes in sleep occur despite this isolation from the natural light‐dark cycle remains a matter of controversy. We measured sleep timing in over 500 university students living in the city of Seattle, WA (47.6°N) throughout the four seasons; we show that even when students are following a school schedule, sleep timing is delayed during the fall and winter. For instance, during the winter school days, students fell asleep 35 min later and woke up 27 min later (under daylight‐savings time) than students during the summer school days, a change that is an hour larger relative to solar midnight. Furthermore, chronotype defined by mid‐sleep on free days corrected for oversleep (MSFc), an indirect estimate of circadian phase, was more than 30 min later in the winter compared with the summer. Analysis of the effect of light exposure showed that the number of hours of light exposure to at least 50 lux during the daytime was a stronger predictor of MSFc than the exposure time to this illuminance after dusk. Specifically, MSFc was advanced by 30 min for each additional hour of light exposure during daytime and delayed by only 15 min for each additional hour of postdusk exposure to light. Additionally, the time of the day of exposure to high light intensities was more predictive of MSFc when daytime exposure was considered than when exposure for the full 24‐h day was considered. Our results show that although sleep time is highly synchronized to social time, a delayed timing of sleep is evident during the winter months. They also suggest that daily exposure to daylight is key to prevent this delayed phase of the circadian clock and thus circadian disruption that is typically exacerbated in high‐latitude winters.